1994
DOI: 10.1128/iai.62.10.4419-4424.1994
|View full text |Cite
|
Sign up to set email alerts
|

Immune response of Brazilian children to a Neisseria meningitidis serogroup B outer membrane protein vaccine: comparison with efficacy

Abstract: Since 1986, serogroup B Neisseria meningitidis has caused approximately 80%Yv of the meningococcal disease in Brazil. In 1988, an epidemic caused byN. meningitidis B:4:P1.15 was recognized in the greater Sio Paulo area of Brazil. The Sfio Paulo state government decided to vaccinate children from 3 to 83 months of age with a vaccine consisting of serotype 4 outer membrane protein and group C meningococcal polysaccharide that was produced in Cuba. About 2.7 million children were vaccinated during two immunizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(67 citation statements)
references
References 29 publications
8
58
0
1
Order By: Relevance
“…In contrast to the clear anti-OMP1 antibody response of immunized patients, the same pattern of antibody response in non-immunized patients was not observed. In agreement with these observations, our previous immunoblot studies of antibody re-sponse of vaccinated children showed that OMP1 was the primary antigen recognized by post-vaccination sera with antibody titers higher than 2 [20]. Similar conclusions regarding the immunogenic potential of OMP1 have been reported by several investigators [14,18,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to the clear anti-OMP1 antibody response of immunized patients, the same pattern of antibody response in non-immunized patients was not observed. In agreement with these observations, our previous immunoblot studies of antibody re-sponse of vaccinated children showed that OMP1 was the primary antigen recognized by post-vaccination sera with antibody titers higher than 2 [20]. Similar conclusions regarding the immunogenic potential of OMP1 have been reported by several investigators [14,18,24].…”
Section: Discussionsupporting
confidence: 90%
“…After vaccination, the proportion of children with bactericidal titer v 2 increased to 24.6%, a proportion similar to the one (25%) found in pre-vaccination sera of children aged 4^6 years. ( [20] and unpublished data). Similar antibody response to another OMP vaccine was described by Boslego et al [12] in Chilean children aged 1^4 years.…”
Section: Discussionmentioning
confidence: 68%
“…130,131 Its immunogenicity and safety in children was demonstrated in a large vaccination study involving toddlers. 132 Recently, the adjuvant eect of MF-59 was shown to be superior to an alum preparation with regard to the antibody response to Hib and N. meningitidis conjugate vaccines when administered to infant baboons. 133 Several formulations including various combinations of immunomodulators (alum, MPL, QS21) incorporated in various w/o and o/w emulsions have been developed and are progressively reaching the stage of clinical trials.…”
Section: Formulations Based On O/w Emulsionsmentioning
confidence: 99%
“…34 Although this is most clearly established for serogroup C disease, it would be surprising if it was different for serogroup B disease. 12,14,35 Immune memory, even if present, as indicated by the height of antibody response following an extra dose after a priming series 31 or after avidity studies, 36 is unlikely to allow a sufficiently rapid response to provide protection. An important delay of about five days has been demonstrated in already primed infants before titre rise after the administration of a booster dose of vaccine.…”
Section: Epidemic Control By Vaccinationmentioning
confidence: 99%